An Informal Group of Hungarians in the Multicultural, Urban Culture of Berlin - Valnerné Török, Eszter (Ethnographica et Folkloristica Carpathica, 2023)
Minority groups leave their traces in the cultural life of cities and it is an important task of science to track down and document these traces. The formation of ethnic communities through self-initiative has been intensively researched and ethnic groups play an increasingly important role in the representation of cities. This study gives a brief insight into the present research work that shows and documents an example of ethnic community organization in the urban space of a large city. The focus of this research is an informal group of Hungarians in Berlin, the Berlin Szalon, which already looks back on 50 years of history. After a brief excursion into the history of salon culture in Berlin, the historical roots of the Berlin Szalon are described. In the second part of this study, some results of an online questionnaire survey carried out amoung the audience of the Berlin Szalon are presented. An important objective of the data collection was to determine the motivation factors and attitude of the salon guests when attending the salon evenings and find out the audience’s opinion of the salon events.